2021
DOI: 10.1556/004.2021.00003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of heat stress on the immune responses of chickens subjected to thermal manipulation in the pre-hatch period

Abstract: Heat stress affects the performance of poultry species and also induces immunosuppression. Chickens can be treated by thermal conditioning to have better heat stress tolerance. Our purpose was to determine the effect of acute heat stress on the immune response, i.e. antibody production against Newcastle disease virus (NDV) and change in the proportion of leukocyte components, in chicks subjected to prenatal heat conditioning. Eighty as-hatched broiler chicks from the same parent stock were used: control (40 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…Monitoring Hatching time from table (1) revealed that through 40 hours (470 to 510 h) there were no significant differences between treatments in 4 first period (from 470 to 502 h), whereas, the significant differences occurs at last period (502 to 510 h), most of chicks in control group were hatched (60.83%), while less chicks had hatched (19.79%) in 2 nd treatment which eggs subjected to changing in temperature at 10 th day of incubation. The results were in line with [55] who use changing in temperature (39.5 1C every 12 h during embryonic days E7-E16), they referred that there were no significant differences in hatching time from 470 onward between treatments group, in contrast to [56] who noticed that use changing in temperature (39.5° C, from 7−16 d for 12 h per d) leading prolong hatching time in treated group and shorter spread of hatch in control group [57].…”
Section: Windows Of Hatchingsupporting
confidence: 82%
“…Monitoring Hatching time from table (1) revealed that through 40 hours (470 to 510 h) there were no significant differences between treatments in 4 first period (from 470 to 502 h), whereas, the significant differences occurs at last period (502 to 510 h), most of chicks in control group were hatched (60.83%), while less chicks had hatched (19.79%) in 2 nd treatment which eggs subjected to changing in temperature at 10 th day of incubation. The results were in line with [55] who use changing in temperature (39.5 1C every 12 h during embryonic days E7-E16), they referred that there were no significant differences in hatching time from 470 onward between treatments group, in contrast to [56] who noticed that use changing in temperature (39.5° C, from 7−16 d for 12 h per d) leading prolong hatching time in treated group and shorter spread of hatch in control group [57].…”
Section: Windows Of Hatchingsupporting
confidence: 82%
“…58 K r sy was a vaccinationist. He firml ybe li e v edth a ts mall po xv acc i nationw ouldreducetheeff ectsoffutureepidemics .Hisgoalw astopro v e the protective power of vaccination through statistical means, and hence its utility,withtheaidof"relativeintensity".Hepresentedthemethodinacom prehensive study at the 11th International Medical Congress in Washington in 1887 59 andthenpublisheditinaseparatevolumein1889, 60 thereby opening a critical debate amongst medical experts. K r systudiedtheprotectivepower of vaccination in quantitative terms.…”
Section: Statisticians and Physicians: The Case Of Medical Statisticsmentioning
confidence: 99%
“…Of particular interest, and due to their elevated core body temperature compared to mammals (~41°C vs. 37°C), high metabolic rate, feather covering, and lack of sweat glands, chickens (meat and egg types) are very sensitive to high environmental temperatures (Perini, Cendron, Rovelli, Castellini, & Cassandro, 2021 ). The detrimental effects of high environmental temperature on feed intake (Abdelli et al., 2021 ; Brugaletta et al., 2021 ; Tabler et al., 2020 ), growth (He et al., 2018 ; Liu et al., 2020 ; Wasti, Sah, & Mishra, 2020 ), welfare (Sesay, 2022 ; Shields, 2015 ), stress (Greene et al., 2022 ; Lin et al., 2006 ; Mahmoud & Edens, 2003 ), immune system (Jahanian & Rasouli, 2015 ; Liu et al., 2022 ; Molnar, Korosi, Balazs, & Gaspardy, 2021 ; Monson et al., 2018 ), and meat and egg quality (Dai et al., 2009 ; Dai et al., 2012 ; Leishman et al., 2021 ; Maynard et al., 2023 ; Zaboli et al., 2019 ) are well documented. Together, these effects consequently result in significant and heavy economic losses to the industry worldwide (Raspoet & Wang, 2022 ; St Pierre, Cabanov, & Schnitkey, 2003 ), in addition to the add capital investment such as fans, cooler pads, and water sprinklers.…”
Section: Introductionmentioning
confidence: 99%